(untitled) (Research, Society and Development, 2022)
The aim of this study is to evaluate the efficacy of different therapeutic regimens using denosumab in patients with giant cell tumor of bone (GCTB), regarding primary outcomes related to therapeutic response (lesion size, pain and function) and presentation to imaging exams, in addition to secondary outcomes related to age (in years) and tumor location, reduction or downgrade of surgical indication, local recurrence, presence of pulmonary metastases and therapeutic side effects. A systematic literature search will be carried out in the PubMed/MEDLINE, Embase (CAPES Journals), Science Direct/Elsevier, Scielo, Cochrane Library and clinical trial records (ClinicalTrials.gov and Registro Brasileiro de Ensaios Clínicos) databases; for exploration of grey literature, the Open Access Theses and Dissertations and the Biblioteca Digital Brasileira de Teses e Dissertações databases will be consulted. We will also conduct a "snowball" survey to identify additional eligible studies for full-text review. Two evaluators will select, extract and assess the risk of bias of the obtained data. If appropriate, a meta-analysis will be carried out, extracting data for the number of events and total patients to perform proportion meta-analysis using the R software, with the "meta" package (version 4.9–6), the "metaprop function" for aspect ratio data. The results of this review will provide convincing information on the efficacy of different therapeutic regimens using denosumab in GCTB, providing a reliable theoretical basis for the research that will follow.